2010
DOI: 10.1128/aem.02335-09
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Persistence and Leaching ofEscherichia coliin Temperate Maritime Soils

Abstract: Enteropathogen contamination of groundwater, including potable water sources, is a global concern. The spreading on land of animal slurries and manures, which can contain a broad range of pathogenic microorganisms, is considered a major contributor to this contamination. Some of the pathogenic microorganisms applied to soil have been observed to leach through the soil into groundwater, which poses a risk to public health. There is a critical need, therefore, for characterization of pathogen movement through th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
65
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(79 citation statements)
references
References 57 publications
(60 reference statements)
5
65
0
1
Order By: Relevance
“…A potential cause could be fresh human sewage input from sewage leakage and overflow; other likely sources include input from animal sources (32) and mobilization of E. coli surviving in the soil (33), sediments (34), and aquatic environment (35). These findings are in agreement with the previously reported observation of severalfold increase in FIB numbers in the surface water bodies after storm events (7)(8)(9).…”
Section: Discussionsupporting
confidence: 83%
“…A potential cause could be fresh human sewage input from sewage leakage and overflow; other likely sources include input from animal sources (32) and mobilization of E. coli surviving in the soil (33), sediments (34), and aquatic environment (35). These findings are in agreement with the previously reported observation of severalfold increase in FIB numbers in the surface water bodies after storm events (7)(8)(9).…”
Section: Discussionsupporting
confidence: 83%
“…Though several authors have isolated E. coli from various natural environments, such as freshwater (4,5), beach water (6, 7), beach sand (7), tropical and subtropical soils (8)(9)(10)(11)(12), coastal temperate forest soils (13), riverine temperate soil (14), and sediments (15), it is difficult to determine unequivocally whether these isolates originated from recent contamination or whether they represent long-term residents in those environments. In 2010, Brennan et al (16) reported the recovery of E. coli populations from intact soil monoliths maintained in lysimeter units (previously described by Ryan and Fanning [17]), which have been protected from fecal contamination since 1998. These long-term soil-persistent E. coli isolates are the subject of the present study.…”
mentioning
confidence: 99%
“…Avery et al (10) observed E. coli persistence in soils amended with cattle, sheep, and swine manure for up to 19 weeks, while Entry et al (11) observed prolonged survival of fecal coliforms and enterococci (at least 42 weeks) in soils amended with dairy manure. Such extended survival in soils can result in the occurrence of indicator organisms in runoff and infiltration waters from sites that have not had prior manure applications for weeks, months, or even years (12,13).…”
mentioning
confidence: 99%